Psycholinguistic and Cognitive Influences on Textual Entailment Misunderstandings in Senior High School - Fajar Biantoro; Yanuarius Yanu Dharmawan (Jurnal Multidisiplin Indonesia, 2024)
The objective of this study is to find out reasons behind common misinterpretation of textual entailment among students in educational settings, focusing particularly on how basic textual concepts impact students' ability to comprehend and analyze texts accurately. The study was carried out at SMA Alam Lampung using twelfth-grade students as participants. It used a qualitative research design and employed saturation sampling procedures to choose its sample. This study aims to explore students' understanding and interpretation skills regarding textual entailment by using questionnaires and interviews as the main data gathering techniques. The results show a significant difference in students' ability to correctly grasp texts and hypotheses, indicating a common misinterpretation of textual entailment principles. Out of 60 replies gathered from 10 questions answered by 6 students each, only 4 solutions adhered to the rules of textual entailment. The other 56 responses showed a misunderstanding of the connection between Text and Hypotheses. The research explores the psycholinguistic and cognitive processes that lead to misconceptions, highlighting the importance of lexical access and comprehending complicated sentence patterns in making valid inferences from texts. It also recognizes the significance of prior knowledge in aiding text understanding and analysis. These results imply that successful educational approaches should go beyond just improving linguistic abilities. They should use tactics designed to help pupils overcome psycholinguistic and cognitive obstacles, so improving their interpretive skills. This study suggests a thorough educational method that combines language skills enhancement with specific tactics to address the psycholinguistic and cognitive barriers affecting students' understanding and interpretation of texts.